Education Program Based Intervention Strategies to Improve School Readiness in Early Childhood: A Systematic Review - Nur, Fatikhatun (The Future of Education Journal, 2025)
In an era of globalization and increasing competition, school readiness has become an essential factor for children’s academic and social success. This article examines the concept of school readiness, which includes cognitive, emotional, social, and physical skills. In Indonesia, regional disparities, cognitive delays, and socioeconomic influences are major challenges in improving children’s school readiness. This study reviews various interventions aimed at enhancing school readiness through a systematic literature review. The research method follows PRISMA guidelines, focusing on education program–based interventions implemented in preschools, kindergartens, and the first year of primary school. The findings indicate that holistic approaches encompassing literacy, self-regulation, executive function, and life skills are key to improving school readiness. Intervention programs such as Getting Ready for School (GRS) and the Sensory Science Project (SSP) have been shown to effectively enhance multiple aspects of children’s readiness. This article provides guidance for practitioners and policymakers to optimize school readiness among children in Indonesia.